Increased impairment of cerebral autoregulation in COVID-19 associated pulmonary failure requiring extracorporeal membrane oxygenation - Thudium, Marcus; Kappler, Jochen; Oremek, Maximilian J. G.; Ehrentraut, Stefan Felix; Kornilov, Evgeniya; Marinova, Milka; Putensen, Christian; Soehle, Martin; Schewe, Jens-Christian (Frontiers in Medicine, 2024)
Introduction Cerebrovascular complications are feared but also commonly reported in patients with COVID-19 requiring extracorporeal membrane oxygenation (ECMO) support therapy. Besides other reasons, a connection between impaired cerebral autoregulation and SARS-CoV-2 infection as a mechanism for an increase in cerebrovascular complications has been hypothesized. Methods In an observational single-center study, we investigated a cohort of 48 patients requiring veno-venous ECMO support therapy with (n = 31) and without SARS-CoV-2 infection (n = 17). Cerebral autoregulation was assessed with the cerebral oximetry-derived autoregulation index (ORx) based on a moving correlation between arterial pressure and cerebral oximetry. Results Patients with ECMO support therapy and SARS-CoV-2 experienced more time with impaired cerebral autoregulation than without SARS-CoV-2 [17 ± 9 vs. 13 ± 9% (p = 0.027)]. Patients with SARS-CoV-2 suffering from cerebrovascular complications had more time with impaired autoregulation than non SARS-CoV-2 patients with these complications (19 ± 9 vs. 10 ± 4%, p = 0.032). Conclusion Our results suggest a connection between SARS-CoV-2 and impaired cerebral autoregulation as well as cerebrovascular complications in SARS-CoV-2 patients.